Investigation of stabilizing internal temperature and humidity of peltierbased cooling refrigerator supplied by small scale PV - Amerrudin, Azizi; Norazlianie, Sazali; Mohd Nizar, Mhd Razali; Muhamad Zahim, Sujod; Ahmad Afif, Mohd Faudzi; Siregar, Januar Parlaungan (Institution of Engineering and Technology, 2022)
The project Investigation of stabilizing internal temperature and humidity of Peltier-based cooling refrigerator supplied by small scale PV. Peltier devices are used for the cooling systems, efficient heat transmission from the module is important. The hotter end of Peltier will be linked to the absorber plate and blade combination. Next, solar panels will be used to collect light energy from sunlight, this will depend on the weather and to put the solar panel at suitable places. Then, the design of the cooling refrigerator had been created to stabilize the temperature and humidity that contains in the cooling refrigerator. Two Peltier devices were used, the expected result of this project is the cooling refrigerator achieved the temperature of 2°C -6°C. The size of the internal cooling box, number of Peltier, temperature surrounding and the values of the good that were put in the cooling box play a huge role for the effectiveness of the project.